Trends in the bills of laws of 2018, to regulate the techniques of artificial reproduction in Peru - Helfer Llerena de Tapia, Olga Mercedes (2018)
The Artificial Production Techniques (APT) generate human life in an artificial way, that is to say without observing the natural process that is the sexual union between male and female. So that, we deem it appropriate to establish bioethics and bio-legal criteria, in the circumstances that the modification of the norm about APT in Peru, will be discussed. For this purpose, with this investigation we analyze the content and consequences of the APT, we analyze the current 7th. article of the General Health Law (GHL), as well as analyze the three bills presented in the last two months to modify article 7 of the GHL; that will allow us to establish the bioethic and bio-legal criteria to regulate the APT abolishing the 7th article of the GHL. The ethic criteria are framed in the interdisciplinary of bioethic, the search for the judicial statute of the conceived and the ethic limits that should rule the science and technology.The results aim to understand that the legal order in Peru is protectionist of the conceived, but not the 7th. article of the GHL authorized by the APT, For involving risks to the life and health of human beings in the state of embryos. Our research provides bioethical and biolegal criteria to regulate the biotechnologies of the beginning of life, putting limits to the TRA, to demand it the the right of human embryos, in accordance with the biological, ontologic and legal statutes.